2007
DOI: 10.1016/j.jsat.2006.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based treatment practices for drug-involved adults in the criminal justice system

Abstract: OBJECTIVE-To estimate the extent and organizational correlates of evidence-based practices (EBPs) in correctional facilities and community-based substance abuse treatment programs that manage drug-involved adult offenders. RESULTS-Most programs offer fewer than 60% of the specified EBPs to drug-involved offenders. In multiple regression models, offender treatment programs that provided more EBPs were community-based, accredited, and network-connected; with a performance-oriented, non-punitive culture, more tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
144
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(149 citation statements)
references
References 65 publications
3
144
2
Order By: Relevance
“…medical, psycho-social, substance abuse treatment, and correctional), and the capacity of organizations to deliver these services. Other papers from this survey have documented that few offenders have access to services in comparison to the overall needs of this population (see Taxman et al, 2007c), and that adoption of innovations varies considerably (see Friedmann et al, 2007;Henderson et al, 2008). These attributes have increased our understanding of the makeup of correctional organizations, and how different characteristics can contribute to the array of services available.…”
Section: Study Limitsmentioning
confidence: 88%
See 2 more Smart Citations
“…medical, psycho-social, substance abuse treatment, and correctional), and the capacity of organizations to deliver these services. Other papers from this survey have documented that few offenders have access to services in comparison to the overall needs of this population (see Taxman et al, 2007c), and that adoption of innovations varies considerably (see Friedmann et al, 2007;Henderson et al, 2008). These attributes have increased our understanding of the makeup of correctional organizations, and how different characteristics can contribute to the array of services available.…”
Section: Study Limitsmentioning
confidence: 88%
“…The community sample used a sampling frame where selection of the counties was based on region and size of the statistical metropolitican area (SMA). A more detailed description of the sampling frame can be found in the work of Taxman et al (2007). This resulted in the selection of 72 counties, with all criminal justice agencies within these counties (e.g.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the relationship between clinicians' intentions and their behaviors is moderated by the organizational barriers. The dual effect of culture and climate on intentions and barriers parallels research on innovation implementation and explains the influence of culture and climate on the adoption, implementation, and sustainment of EBTs and other innovations that has been established in many studies (1,4,9,14,18,21,29,55,56,64,75,112). Evidence has also shown that organizational culture impacts other employee behaviors (e.g., turnover) directly and indirectly through its effects on organizational climate (3,51,111).…”
Section: Mechanisms That Link Organizational Interventions and Socialmentioning
confidence: 90%
“…The importance of this funding to community agencies needs to be weighed in the context of the Resource Dependency Theory against the demands of increased professionalization of the workforce and movement toward evidence-based practices (Friedman, Taxman, & Henderson, 2007). Although many administrators were not happy with the lower reimbursement rate that DOC provided, they complimented the ease of managing the contract and regulations, particularly in comparison with private funding that necessitated a great deal of oversight and staff time with cumbersome verifications.…”
Section: Discussionmentioning
confidence: 99%